Perbedaan Tarif Transportasi Umum Antara Penumpang Umum dan Pelajar Atau Mahasiswa Menurut Hukum Islam - Kamalulloh, Colungga Afgan; Mualim, Mualim; Matangaji, Amaludin (AL-MASHALIH (Journal of Islamic Law), 2025)
Public transportation plays an important role in supporting the mobility of society, especially in areas where not all residents own private vehicles. One common policy implemented by public transportation providers is the fare differentiation between general passengers and students. This study focuses on P.O Elf Bayem AKDP Kuningan - Cirebon, which applies different fares based on passenger categories. The main issues examined are how this fare differentiation is implemented and how Islamic law views such a practice. The purpose of this research is to understand the implementation of fare differences between general passengers and students, and to analyze this practice based on the principles of Islamic law, particularly the ijarah contract. This study employs a qualitative method with a field research approach. Data collection techniques include interviews with operators, drivers, and service users, supported by relevant documentation. The findings reveal that the practice of fare differentiation at P.O Elf Bayem AKDP Kuningan - Cirebon aligns with the principles of ijarah in Islamic law. Especially ijarah 'ala al-a'maal ijaarah. This practice fulfills three important elements: first, there is transparency of rates in accordance with Al-Ahzab verse 70; second, an agreement based on mutual consent (antaraḍhin) as in An-Nisa verse 29; and third, there is no element of injustice, as emphasized in the Hadith of Abu Dawud, No. 3451. Therefore, this practice can be considered legitimate and in accordance with the values of muamalah in Islamic law.